Characteristics of hydraulic resistance and velocity profile in vegetated open-channel flows - Nguyen, Hoai Thanh (2012)
The presence of vegetation in open-channel flow has significant influences on flow resistance and turbulence structures. This study sets out aims to evaluate the flow resistance and scale velocity profile in depth-limited flow conditions. It carries out experiments to simulate rigid vegetation under emergent and submerged flow conditions. By drawing analogies between pipe flows and vegetated channel flows, the study proposes a new friction function for emergent flow conditions which clearly shows a monotonic decrease of the drag coefficient using the new Reynolds number defined using a vegetation-related hydraulic radius. In addition, by transforming the concept of hydraulic radius, a representative roughness height is proposed for quantifying effect of submerged vegetation on flow resistance in the surface layer which performs better than other length scales in collapsing resistance data collected under a wide range of vegetation conditions. An approach is then developed for estimating the average flow velocity and resistance coefficients for both cases of rigid and flexible vegetation. Finally, the study proposes a length scale metric that normalizes velocity profiles of depth-limited open channel flows with submerged rigid vegetation using the plane mixing layer analogy. The proposed scaling is better than those based on the logarithmic, velocity-defect and power laws in collapsing the velocity profiles. A simple viscosity model is developed to justify the scaling argument.